MARRIAGE SYSTEM OF THE SANTALS OF MAYURBHANJ OF ODISHA IN EASTERN INDIA - hembram, Singo; Mopatra, Ratnakar (International Journal of Psychosocial Rehabilitation, 2020)
This paper attempts to study the marriage system of Santals of Mayurbhanj District of Odisha. Marriage is social institution of Santals.Marriage is considered necessary for a biological and psychological need and to survive in general. Without joyful night by singing, dancing, drumming and playing flutes Santal marriage is not considered. The significance of tradition, culture and value system of Santal are gradually losing their meaning to the young and educated Santal. This paper would highlight the changes in traditional marriage system of the Santals of Mayurbhanj District of Odisha in Eastern India.